Capecitabine-induced Hand-foot Syndrome with Hyperpigmentation on Oral Mucosa and Nails: A Rare Entity - Suprit Malali; Sourya Acharya (Journal of Clinical and Diagnostic Research)
Dear Editor, We present two cases of Capecitabine-induced Hand-Foot Syndrome (HFS), hyperpigmentation on the oral mucosa, and nails. Case 1 A 28-year-old female, previously diagnosed with stage 4 left-sided inflammatory breast cancer, along with metastases to the right breast and skeletal sites one year ago, as confirmed by trucut biopsy and Positron Emission Tomography scan (PET), presented to our clinic with complaints of fatigue and generalised weakness persisting for the last month. The patient does not report any co-morbidities. Further clinical assessment and investigation are warranted to address the current symptoms and determine the appropriate course of management for the underlying cancer and associated symptoms. She received four cycles of injectable capecitabine and cyclophosphamide and later was shifted to oral chemotherapy with the same drugs for the last six months. All routine investigations such as complete blood count, liver function test, kidney function test, coagulation profile, and random blood sugar were within normal limits. The chest X-ray was normal. The Electrocardiogram (ECG) was suggestive of normal sinus rhythm. Upon examination, vitals were normal, and hyperpigmented patches and macules with blackish to grey colour were seen in the oral mucosa, gingival mucosa, teeth, palmar and dorsal aspects of hands, and plantar and dorsal aspects of the foot [Table/Fig-1a-d,2a-d].